Comprehensive Review of Pharmacist-Driven Medication Therapy Management: Improving Patient Safety and Compliance - Balhareth, Ibrahim Mohsen Salem; Al shalan, Mohammed Ahmed Mohammed; Alshehri, Abdullah Mahdi Mohammed; Alshehri, Abdullah Mohammed Abdullah; Alshehri, Dhafer Mohammed Dhafer; Alshahrani, Abdullah Ali Saeed; Al rashadi, Saeed Mohamad Rashadi; Alqahtani, Faris Hussain Ali; Alhudaisan, Thamer Mohammed; Alwadai, Abdullah Mahdi Jobran; Alhassan, Fatimah Mohammed; AlSufian, Tahani N.; et al. (Journal of Ecohumanism, 2024)
Medication therapy management is a critical service that involves medication reviews, patient education, and care management to enhance patients' therapeutic processes. The presence of pharmacists as easily available healthcare professionals who specialize in the use of drugs and medication is vital in avoiding causes of medication risks and complications, medication compliance, and better outcomes for patients’ health. This review will discuss the involvement of pharmacists in MTM, the advantages or disadvantages of using the technique, patient safety, and noncompliance. We also review how MTM interventions conducted by pharmacists are being practiced and evaluated in the present literature, their strengths and weaknesses, and the future direction of this practice.